How does urbanization affect public health? New evidence from 175 countries worldwide - Zhang, Zhenhua; Zhao, Mingcheng; Zhang, Yunpeng; Feng, Yanchao (Frontiers in Public Health, 2023)
Urbanization is an essential indicator of contemporary society and a necessary historic stage in the industrialization of all countries. Thus, we explore the impact of urbanization on public health using the OLS estimation and a two-way fixed effect model based on annual panel data from 175 countries from 2000 to 2018. This paper also addresses potential endogeneity issues and identifies causal relationships using the coefficient stability tests, system GMM, and instrumental variable method. The results demonstrate that urbanization positively affects public health. Furthermore, we find that the impact of urbanization on public health can be mediated through living standards, and nations with higher living standards reduce the effect of urbanization on public health. An increase in the urbanization rate can promote public health by improving residents' living standards. Our results have significant real-world implications for the research of urbanization and the formulation of public health policy.